2013
DOI: 10.1001/jamaoto.2013.2821
|View full text |Cite|
|
Sign up to set email alerts
|

Dexamethasone for the Prevention of Recurrent Laryngeal Nerve Palsy and Other Complications After Thyroid Surgery

Abstract: Importance: Recurrent laryngeal nerve dysfunction and hypoparathyroidism are well-recognized, important complications of thyroid surgery. The duration of convalescence after noncomplicated thyroid operation may depend on several factors, of which pain and fatigue are the most important. Nausea and vomiting occur mainly on the day of operation. Glucocorticoids are well known for their analgesic, anti-inflammatory, immunemodulating and antiemetic effects. However, there is little information in the literature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…Supporting this hypothesis is a systematic review that analyzed 27 studies with over 25,000 cumulative thyroidectomy patients and found 9.8% and 2.3% mean incidences of temporary and permanent post-thyroidectomy vocal fold paralyses 22 , which are nearly identical rates to those in the present study (9.5% overall, 2.1% “permanent”/requiring intervention). More reinforcing evidence is gained from studies that actively examined patients immediately post-operatively from thyroidectomy and reported similar rates to those herein (4.9 – 8.4%) 46,47 . Interestingly, Bergenfelz et al .…”
Section: Discussionsupporting
confidence: 82%
“…Supporting this hypothesis is a systematic review that analyzed 27 studies with over 25,000 cumulative thyroidectomy patients and found 9.8% and 2.3% mean incidences of temporary and permanent post-thyroidectomy vocal fold paralyses 22 , which are nearly identical rates to those in the present study (9.5% overall, 2.1% “permanent”/requiring intervention). More reinforcing evidence is gained from studies that actively examined patients immediately post-operatively from thyroidectomy and reported similar rates to those herein (4.9 – 8.4%) 46,47 . Interestingly, Bergenfelz et al .…”
Section: Discussionsupporting
confidence: 82%
“…Care should be taken in cases of hyperparathyroidism not to cause a further significant elevation of serum calcium. Dexamethasone (8 mg intravenously [IV]) given 90 minutes before skin incision is not yet a standard but has been shown to reduce the rate of transient hypoparathyroidism and laryngeal nerve palsy in a single 2013 study (15).…”
Section: Mitigation Of Postoperative Hypoparathyroidismmentioning
confidence: 99%
“…In keeping, other investigators reported that a comparable single shot of intraoperative steroids did not reduce postoperative RLN palsy rates, shortening only the recovery time for transient vocal fold palsies from 40.5 to 28.6 days . The roles of edema or vasospasm which steroids may help decrease are not well established pathophysiologically for RLN injury and the hypothetical benefit of calcium channel blockers …”
Section: Discussionmentioning
confidence: 96%
“…17 The roles of edema or vasospasm which steroids may help decrease are not well established pathophysiologically for RLN injury and the hypothetical benefit of calcium channel blockers. 18,19…”
Section: Recovery Of Postoperative Vocal Fold Function After Losmentioning
confidence: 99%